Alterations in AP-1 and AP-1 Regulatory Genes during HPV-Induced Carcinogenesis - Jillian de Wilde; Johanna De-Castro Arce; Peter J. F. Snijders; Chris J. L. M. Meijer; Frank Rösl; Renske D. M. Steenbergen (Cellular Oncology)
Background: Previous studies demonstrated a functional involvement of the AP-1 transcription factor in HPV-induced cervical carcinogenesis. Here, we aimed to obtain further insight in expression alterations of AP-1 family members during HPV-mediated transformation and their relationship to potential regulatory (Notch1, Net) and target (CADM1) genes.